The Roles of Carbohydrate-Electrolyte Solutions in Athlete Hydration Status and Performance : A Narrative Review - Ervira Wahyuni; Diana Sunardi; Bernie Endyarni Medise (Universitas Pendidikan Indonesia, 2024)
Dehydration is prevalent among athletes. Dehydration may cause fluid and electrolyte imbalance and impairment of an athlete physical and cognitive performance. Carbohydrate electrolyte solutions (CES) are often used by athletes as a rehydration fluid because it is claimed to have numerous beneficial effects on hydration status and performance. Studies on the use of carbohydrate-electrolyte solutions showed mixed results. Some studies also highlighted the side effects of carbohydrate-electrolyte solutions on gastrointestinal system. This review aimed to summarize the roles of carbohydrate-electrolyte solutions on hydration status and performance of athletes. The literature review was conducted in the narrative type. Database search was conducted using Pubmed Central search engine. The search terms used were